Research on types of gas reservoirs divided by seepage capacity and their seepage mechanism, law and productivity - Jianzhong Zhang; Shusheng Gao; Huaxun Liu; Liyou Ye; Wenqing Zhu; Weiguo An (Energy Reports, 2023)
In view of the diversity of gas reservoir classification and the differences of characteristics of geology and development in different gas reservoirs, it is necessary to study the adaptability of gas reservoir classification. This paper analyzes and summarizes the current classification methods of gas reservoirs, studies the microscopic pore characteristics and seepage mechanism of different gas reservoirs. The commonalities and individualities of seepage laws in different gas reservoirs are determined, the key factors that determine the development dynamics and effects of gas reservoirs are proposed, and the gas reservoirs types are divided from the perspective of development. The results show that the development characteristics of gas reservoirs are determined by the seepage law, and the seepage law is determined by the microscopic pore characteristics. Therefore, from the perspective of development, the microscopic pore characteristics are the fundamental of gas reservoir classification. Gas reservoirs can be divided into four types: tight, low permeability, medium and high permeability, and fractured. This classification method can unify the types of gas reservoirs according to the seepage laws of different gas reservoirs, establish corresponding seepage models, evaluate productivity, and predict performance. It is of great significance for rational, efficient and scientific development of gas fields.